Haplotype analysis of Bangladeshi β-thalassaemia patients: A pilot study - Bashar, Amae; Moosa, MM; Ayub, MI; Rahaman, MH; Sarwardi, G; Khan, W; Khan, H; Yeasmin, S (Dhaka University Journal of Biological Sciences, 2022)
β-thalassaemia is one of the major genetic disorders in Bangladeshi population. Nevertheless, systematic study on the genetic basis of this disease in Bangladeshi population is very limited. The major aim of this study was to identify and characterize the β-globin gene cluster haplotype in Bangladeshi β-thalassaemia patients. For this, β-thalassaemia patients diagnosed on haematological observations were tested at the genetic level for different β-globin cluster haplotypes. Twenty-eight β-globin gene clusters of fourteen confirmed β-thalassaemia patients were analyzed using PCR amplification and Restriction Fragment Length Polymorphism (RFLP). Type VII haplotype was found to be the most common β-globin gene cluster haplotype in the studied population. Two of the patients had Type VII haplotype in homozygous form. Only one patient had atypical haplotype in one locus. The study reports β-globin cluster haplotype of fourteen Bangladeshi patients for the first time. However, it should be noted that small size precludes the possibility of determining the detailed distribution of different haplotypes and their association with different β-thalassaemia mutations. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 479-486, 2022 (June)